Effects of innovation on the growth of Ecuadorian firms: a quantile analysis - Rodeiro-Pazos, David (2018)
This paper analyzes the relationship between firms’ innovation and growth measured by sales and labor productivity in Ecuador. The literature on this topic has focused mainly on developed countries. We apply panel data quantile regressions to analyze a sample of 99,872 private limited company and public limited company for the period 2000-2013. Quantile regression allows us to avoid conventional analysis through the study of the average impact for the average company, which can lead to the discovery of phenomena underlying relationships. The results show that firm innovation has a negative on productivity growth. In contrast, there is a positive relationship between innovation and sales growth for firms in some quantiles. These results lead us to establish a series of recommendations aimed at public policy decision-makers. In particular, the support of government entities is important for a company's R&D activities, which contribute to generating profitable intangible assets. This support can be through advice, subsidies, or tax benefits, among others. At the country level, government effort to protect intangible assets is also important, promoting competitive advantages for those companies that actually invest or buy such assets.